2021
DOI: 10.3389/fneur.2021.739267
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Acute Stroke Due to Large-Vessel Occlusion Presenting With Mild Symptoms

Abstract: Purpose: To evaluate the safety and efficacy of mechanical thrombectomy (MT) for acute stroke due to large vessel occlusion (LVO), presenting with mild symptoms.Methods: A prospective cohort study of patients with mild ischemic stroke and LVO was conducted. Patients were divided into two groups: MT group or best medical management (MM) group. Propensity score matching (PSM) was conducted to reduce the confounding bias between the groups. The primary outcome was functional independence at 90 days. The safety ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, no RCTs have been conducted on this matter, and observational research has produced contradictory findings. Our findings corroborated the findings of the retrospective research in patients with LVO and moderate symptoms (NIHSS 0–5), thrombectomy was linked to better clinical outcomes than medicinal treatment 27 . Additionally, a 2018 meta-analysis found that thrombectomy had positive results for LVO stroke patients with little or mild symptoms (NIHSS 8) 28 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To the best of our knowledge, no RCTs have been conducted on this matter, and observational research has produced contradictory findings. Our findings corroborated the findings of the retrospective research in patients with LVO and moderate symptoms (NIHSS 0–5), thrombectomy was linked to better clinical outcomes than medicinal treatment 27 . Additionally, a 2018 meta-analysis found that thrombectomy had positive results for LVO stroke patients with little or mild symptoms (NIHSS 8) 28 .…”
Section: Discussionsupporting
confidence: 90%
“…An elevated risk of sICH may be linked to several MT passes. Since the invention of the thrombectomy procedure about 10 years ago, patients in this research have seen fewer problems and deaths 27 . Overall, primary concerns with MT in patients with mild stroke remain revolve around sICH and associated sequelae.…”
Section: Discussionmentioning
confidence: 95%